1997
DOI: 10.1016/s0895-7061(96)00507-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Antihypertensive Medication Does Not Exacerbate Sleep-Disordered Breathing in Newly Diagnosed Hypertensive Patients

Abstract: It has been speculated for some time that various antihypertensive medications may have a deleterious effect on respiration during sleep and thereby enhance the apparent association between hypertension and sleep apnea/hypopnea (SAH). However, there are few data to support this contention. The present study used a double-blind, randomized, cross-over design to contrast the effects of 6 weeks treatment with alpha-methyldopa and the combination of hydrochlorothiazide and amiloride with that of amlodipine and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Means and standard deviations (SD) for the OSA outcomes were extracted from preintervention and postintervention assessments. Medians were used to impute missing means and range/4 to impute missing SD 28,29 as prescribed in the metaanalysis literature. 30 A within-subject correlation of 0.4 was assumed between pre-post outcome measurements to approximate the SD of pre-post differences if not reported.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Means and standard deviations (SD) for the OSA outcomes were extracted from preintervention and postintervention assessments. Medians were used to impute missing means and range/4 to impute missing SD 28,29 as prescribed in the metaanalysis literature. 30 A within-subject correlation of 0.4 was assumed between pre-post outcome measurements to approximate the SD of pre-post differences if not reported.…”
Section: Data Extractionmentioning
confidence: 99%
“…30 A within-subject correlation of 0.4 was assumed between pre-post outcome measurements to approximate the SD of pre-post differences if not reported. The severity of sleep apnea was reported as RDI in two trials 5,28 and AHI in the rest of the trials. Two trials reported posttreatment AHI or RDI for rapid eye movement (REM) and non-REM sleep separately; however, sufficient information was available to allow for computation of AHI or RDI based on total sleep time, which was then used in subsequent analyses.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…No change of the AHI is observed with any class of antihypertensive drugs, including a-methyldopa and b blockers, which have central actions, Calcium (Ca) antagonists or angiotensin-converting enzyme (ACE) inhibitors, indicating that none of the known classes of antihypertensive drugs may exert any specific effect on OSAS itself. 32,33 An assessment conducted on a small number of patients showed that b blockers significantly reduced diastolic BP measured on clinical examination compared with Ca antagonists, ACE inhibitors, angiotensin receptor blockers and diuretics. Another report showed significant reduction of the nocturnal systolic and diastolic BP levels following treatment with b blockers compared with Ca antagonists, ACE inhibitors and angiotensin receptor blockers, although there was no significant difference in the degree of reduction of daytime BP during awakening, nor any difference compared with diuretics.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Two studies have shown an increase in TST and SE (Bartel et al, 1997;Foral et al, 2003) on methyldopa and others have found decreased SWS and REM sleep (Foral et al, 2003). Two studies have shown an increase in TST and SE (Bartel et al, 1997;Foral et al, 2003) on methyldopa and others have found decreased SWS and REM sleep (Foral et al, 2003).…”
Section: Alpha 2 Agonistsmentioning
confidence: 99%